Development of Android-Based Interactive Learning Media for Polyhedra Using the ADDIE Model - Syakinnah, Amalia Nurhayati; Linuhung, Nego; Vahlia, Ira (Faculty of Teacher Training and Education, 2026)
The integration of technology in mathematics learning is essential to overcome students’ difficulties in visualizing abstract concepts, particularly polyhedra. This study aims to develop an Android-based interactive learning media and to determine its validity and practicality. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study involved three material experts, three media experts, and 10 junior high school students in a limited trial. Data were collected using expert validation sheets and student response questionnaires, and analyzed using descriptive percentage techniques. The results showed that the developed media achieved a validity level of 82% from material experts and 90% from media experts, both categorized as very valid. Furthermore, the practicality test conducted on students resulted in a score of 86%, which is categorized as very practical. These findings indicate that the developed media is feasible and supports students in understanding and visualizing polyhedra concepts. In conclusion, the Android-based interactive learning media developed through the ADDIE model is valid and practical as supplementary learning media. It has the potential to enhance students’ motivation, independence, and learning outcomes in mathematics learning.